The Effect of Fertilizer Subsidies on Farming Sustainability, A Systematic Review of Economic, Social, and Environmental Dimensions: A Systematic Literature Reviews - Muhammad Lukman Nulhakim; Fitria Dina Riana; Tri Wahyu Nugroho (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
This study examines the impact of fertilizer subsidy policies on the sustainability of farming businesses through a comprehensive systematic review of economic, social, and environmental dimensions. Using the PRISMA methodology, the study analyzed 24 selected articles from the database. Scopus and Web of Science published in the period 2015-2025. The study results show that fertilizer subsidies provide significant economic benefits in the form of reduced production costs, increased income, and farmer productivity, although they can create long-term dependency. From a social aspect, subsidies improve farmer welfare, strengthen resilience to climate change, and encourage social cohesion, but have the potential to cause inequality in the distribution of benefits between farmer groups and regions. An environmental perspective reveals that chemical fertilizer subsidies often encourage excessive use that has a negative impact on soil quality, water, and greenhouse gas emissions, while organic fertilizer subsidies and precision technology have the potential to mitigate environmental damage. This study recommends reformulating subsidy policies with a holistic approach that integrates economic, social, and environmental considerations to support the transition to sustainable agricultural practices through a combination of targeted subsidy strategies, farmer capacity development, and adoption of environmentally friendly technologies.    Keywords: Fertilizer Subsidy, Sustainability of Farming, Economic Dimension, Social Dimension, Environmental Dimension